2017
DOI: 10.3130/jaabe.16.655
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting Occupancy for Demand Driven HVAC Operations Using Time Series Analysis

Abstract: Building heating, ventilation, and air conditioning (HVAC) systems contribute substantially to the energy consumption of buildings. Today, traditional HVAC systems mostly operate according to the maximum occupancy assumption, which in turn increases energy consumption during periods of low occupancy. Although, recently, implementing demand-driven HVAC operations are accepted as an innovate approach for reducing HVAC-related energy consumption, occupancy forecast is important to realize demand-driven HVAC opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In the analysis of consecutive data, the multiplicative decomposition approach is preferred. Therefore, in this study, this approach was used, in which time series can be expressed as the product of the four components of the series and are Y = T.S.C.I, where Y represents the original data, whereas T, S, C, and I represent the trend, seasonal, cyclical, and random components of the series, respectively (Calis et al 2017). In this method, first, the effect of the random change is reduced by applying an exponential correction to the data.…”
Section: Methodsmentioning
confidence: 99%
“…In the analysis of consecutive data, the multiplicative decomposition approach is preferred. Therefore, in this study, this approach was used, in which time series can be expressed as the product of the four components of the series and are Y = T.S.C.I, where Y represents the original data, whereas T, S, C, and I represent the trend, seasonal, cyclical, and random components of the series, respectively (Calis et al 2017). In this method, first, the effect of the random change is reduced by applying an exponential correction to the data.…”
Section: Methodsmentioning
confidence: 99%
“…Python language is used to identify the SARIMA models. The construction of the models by means of Box-Jenkins procedure [3], [5] has the following steps:…”
Section:  Fundamentals Of Sarima Modellingmentioning
confidence: 99%
“…In addition, Azizpour et al (2013) indicated that the actual thermal dissatisfaction of occupants in a hospital was greater than the predicted dissatisfaction obtained via the PMV-PPD model. Apart from building and climate-related characteristics, some research indicated that occupant-related parameters such as gender and age also have a correlation with thermal complaints (Ceria and De Dear 2001;Choi et al 2010;Calis et al 2018). It can be concluded that predicting thermal complaints is not an easy task.…”
Section: Introductionmentioning
confidence: 99%